Cataract surgery with coexisting corneal degeneration - Aditi Jhori; Mona Bhargava; Debasmita Bera (Indian Journal of Ophthalmology)
Background: Corneal degenerations is an all-inclusive term encompassing a broad spectrum of entities that result from physiological changes secondary to aging, as sequelae to environmental insult, or as an ocular manifestation of systemic diseases or long-standing local inflammation. They are often peripheral and eccentric. They may result in vision loss, ocular pain, and reduced depth perception, and limit patient’s ability to focus well. Degenerations are mostly sporadic and manifest late in life, thus highlighting their coexistence when dealing with cataract surgeries in the concomitant settings of corneal degenerations. Purpose: Cataract with coexisting corneal degeneration poses certain unique challenges. Synopsis: In this video, we have highlighted the challenges of cataract surgery in a patient with Terrien’s marginal degenerations and Salzman nodular degenerations. Preoperative management, evaluation, intraocular lens power calculation, and postoperative outcome in cases with coexisting diseases along with case-based examples are presented. Highlights: In patients of cataract with coexisting corneal degenerations, the critical point is to ensure that the corneal findings are relatively stable. Any surgical planning is quickly invalidated if the disease is actively progressing. It is important to consider location of wound placement and optimization of surgical view in these patients undergoing cataract surgery. Visual prognosis is good, but regular monitoring is required. These cases highlight the importance of addressing the refractive sequelae of coexisting corneal degenerations when planning cataract surgery, to ensure minimal postoperative astigmatism and achieve favorable outcomes. Video link: https://youtu.be/JONMwZiKxMs